Análisis del anticipo del impuesto a la renta y su impacto económico en las empresas de Manabí, periodo 2014-2018 - Bazurto Zambrano, María Lisbeth (2021)
The present investigation was developed in Manabí Province, which objetive was to analyze the advance payment of income tax in order to measure the economic impact that this caused to companies in this province during the period from 2014 to 2018. In the development of the theoretical framework, the definitions corresponding to the tax collection and the calculation method for the advanced payment are exposed. For the data collection in the research process, the deductive, descriptive and analytical methods were used, accompanied by toolssuch as the questionnaire, which was of vital importance because through it a panorama of how the advance has affected in the companies. Free interviews were used, with which a clear perspective was obtained in the tax area with issues related to the collection of the income tax advance. Through a database, the information from the financial statements of the companies was compiled to later be graphed and analyzed to have a better interpretation. By means of the SPSS statistical program, the results obtained from the surveys were tabulated and the Pearson correlation was also carried out. These tools were of great help to simplify the investigation and meet each of the proposed objectives.